PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI). UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IIIA SDN 9 DURI BARAT KECAMATAN MANDAU KABUPATEN BENGKALIS - br Harianja, Nurmauli; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This Research was conducted because of the results a learning of mathematical class IIIA SD Negeri 9 Duri Barat Kecamatan Mandau. From 35 students who reached KKM about 20 people ( 57,14 %) and students who did not be completed 15 people ( 42,86 % ) with an average 65,45 .The purpose of this research to increase yields of learn math students IIIA SD Negeri 9 Duri Barat Kecamatan Mandau by the application of math education realistic Indonesia. The results obtained by the average value of 65,45 basic score increased in the first cycle of 26,11 % to 81,28. In the second cycle the average value of student also increased by 38,21 % to 89,08. On the basis of completeness score mathematics students only 57,14 %. After teachers implement setrategi math education realistic Indonesia ( PMRI) in the first cycle classical completeness increased to 89,57 %, the second cycle of classical completeness obtained are increased to increase to 97,14 %. Activities of teachers at the first meeting of 75,00 % to a category good. The second meeting increased to 80,00 % to a category good. In the scond cycle increased to 85,00 % to a category is good. At a meeting of the second meeting of the scond cycle, the activities of teachers increased to, 90,00 % to a category is good. Activities of students in the first cycle of the first meeting have presentase 70,00 % to a category good. In the second increased to 80,00 % to a category good. At the first meeting of the scond cycle of student activity increased to 80,00 % to a category good and at the second meeting of the scond cycle increased again to 90,00 % to a category good. Thus can be concluded that the implementation of math education realistic Indonesia ( PMRI) to improve learning outcomes mathematics students class IIIA SD Negeri 9 Duri Barat Kecamatan Mandau Key words: math education realistic Indonesia, study results mathematics